The Effect of Employee Performance on the Effectiveness of the Finance and BMN Subdivisions at the Regional Office of the Ministry of Religion of North Sumatra - Nur Atika Tanjung; Sri Sudiarti (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
Employees are expected to be more proactive in finding new ways to improve business efficiency and effectiveness. When an organization reduces the number of employees, it becomes more dependent on the existing employees to do something than what is assigned to them. The sources of data used come from two sources, namely primary data and secondary data. The data collection method used is through interviews and documents. Interviews were conducted in depth so that the information obtained was more detailed than the experience of the reporter. The results of determining the correlation coefficient above indicate that the performance of workers on work efficiency is 67.40% while 32.60% is influenced by other factors. The quality of work has a major impact on the performance of the Regional Office staff of the Ministry of Religion of North Sumatra. And there is a significant influence between performance and effectiveness at the Regional Office of the Ministry of Religion of North Sumatra together, and the results seem to indicate that the value of these two factors greatly affects employee performance.